Two Centuries of Price-Return Momentum. Issue 5 (1st September 2016) - Geczy, Christopher C.; Samonov, Mikhail
Abstract : Having created a monthly dataset of US security prices between 1801 and 1926, we conduct out-of-sample tests of price-return momentum strategies that have been implemented in the post-1925 datasets. The additional time-series data strengthen the evidence that price momentum is dynamically exposed to market risk, conditional on the sign and duration of the trailing market state. On average, in the beginning of positive market states, momentum's equity beta is opposite to the new market direction, which generates a negative contribution to momentum profits around market turning points. A dynamically hedged momentum strategy significantly outperforms the unhedged strategy. Abstract : Editor's note: This article was reviewed and accepted by Executive Editor Stephen J. Brown. Authors' note: We make frequent use of factor models that include momentum (the topic of this article) in our asset management, consulting, and other activities at Forefront Analytics and GKFO.